(untitled) (Applied Biological Research, 2023)
Herbal wines are rich decoction of active secondary metabolites of plants. The consumption of herbal wines imparts health benefits to the consumers because of their antioxidant and antimicrobial properties. In light of the increasing demand for value-added herbal products, the present study aimed to develop a production process for herbal wine from aloe vera and ginger juices. The prepared herbal wines were evaluated for their antimicrobial properties against food-borne pathogens. Aloe vera and ginger juices were adjusted to TSS level of 20° Brix by adding honey. The juices were subjected to fermentation using an active culture of Saccharomyces cerevisiae at 28°C. Various fermentation parameters like pH, TSS, reducing sugars, and ethanol concentrations were periodically measured. The wine samples were analysed for titratable acidity, total phenolic content, and antimicrobial potential by standard methods. The aloe-vera and ginger wines showed final titratable acidity of 0.09 and 0.16; a ºBrix to acid ratio of 66.6 and 56.2, respectively, in a fermentation period of 20 days. Total phenolic content was 34.5 ± 0.28 for aloe vera wine and 179.6 ± 0.56 for ginger wine. The alcohol content of aloe vera and ginger wine was 8.29 and 7.91 with fermentation efficiency of 97.8 and 96.2, respectively. Both herbal wines exhibited antimicrobial activity against food-borne pathogens, E. coli and Bacillus cereus. These wines can be accepted as safe and healthy drinks as they retained good phytochemical characteristics.